Profiling of cMET and HER family receptor expression in pancreatic ductal adenocarcinomas and corresponding lymph node metastasis to assess relevant pathways for targeted therapies: looking at the soil before planting the seed - Muckenhuber, Alexander; Jesinghaus, Moritz; Bergmann, Frank; Stenzinger, Albrecht; Weichert, Wilko (Pancreas, 2016)
Objectives Comprehensive assessment of cMET and HER family receptor tyrosine kinases expression, changes of expression during metastatic progression, amplification status of the MET gene, and correlations with patient characteristics in pancreatic ductal adenocarcinoma (PDAC) was conducted. Methods We investigated 56 PDACs and corresponding lymph node metastases for HER1 to HER4 and cMET expression by immunohistochemistry, as well as cMET gene copy numbers by chromogenic in situ hybridization. Results Of all receptor tyrosine kinases evaluated, cMET expression was highest with 46.5% of tumors showing moderate or strong expression and a weak correlation with gene copy number status (P = 0.04; Spearman ρ = 0.28). cMET expression was increased in metastases. In contrast, expression levels of HER family receptors were generally low both in primaries and metastases. A weak yet significant correlation of HER1 and cMET expression levels was observed (P < 0.001; Spearman ρ = 0.44) and HER1 was often present in poorly differentiated tumors (G3, P = 0.049). Conclusions Our data suggest that cMET might constitute an interesting molecule for combining targeted and chemotherapeutic approaches in PDAC, because expression is frequent and increased during metastatic progression. In PDAC, cMET protein expression might be a more useful stratification biomarker than cMET gene amplification, which does not seem to be its primary regulator.